Incidental Findings in Male Breast Carcinoma: A Genetic Counseling Approach. (1st September 2016) - Chatterjee, Manjima; Sheela, M.L.; Mukherjee, Upasana; Patil, Shekar; Satheesh, C.T.; Murugan, Krithika; Naik, Radheshyam; Rao, Nalini; Mahesh, B.; Mannan, U. Ashraf; Gupta, Vaijayanti; Sankaran, Satish; et al.
Abstract: Male breast carcinoma (MBC) is a rare cancer type that accounts 1 percent of the total breast cancer cases. This substantially invites diagnosis challenges and social burdens where the individual needs more personalized therapies and genetic counseling to cope with the condition. This study aims to analyse a total of four male breast cancer cases with or without secondary recurrence. Tissue or saliva samples were analysed with informed and written consent for each individual subjecting to next generation sequencing aiming high throughput investigations. The results revealed two cancer syndromes in an individual with breast and thyroid carcinoma and mutations in PI3KCA, PTEN, NBN, RB1 genes. The rest three cases were identified with alterations in NBN, BRIP1 and BRCA2 mutations. Genetic counseling was provided to each participant and the responses were noted upon post-test targeted therapies.